2016
DOI: 10.1002/jbt.21821
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Quercetin on Neurochemical and Behavioral Deficits in Rotenone Rat Model of Parkinson's Disease: Modulating Autophagy (Quercetin on Experimental Parkinson's Disease)

Abstract: Autophagy is necessary for neuronal homeostasis and its dysfunction has been implicated in Parkinson's disease (PD) as it can exacerbate endoplasmic reticulum (ER) stress and ER stress-induced apoptosis. Quercetin is a flavonoid known for its neuroprotective and antioxidant effects. The present study investigated the protective, autophagy-modulating effects of quercetin in the rotenone rat model of PD. Rotenone was intraperitoneally injected at dose of 2 ml/kg/day for 4 weeks. Simultaneous intraperitoneal inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…It also inhibits lipid peroxidation and platelet aggregation, and it stimulates mitochondrial biogenesis [32]. Several studies have reported on the neuroprotective effects of quercetin, both in vitro and in vivo models of neurodegenerative disorders, such as cognitive impairment [33], ischemia, traumatic injury [34], Parkinson's disease (PD) [35], and Huntington's disease (HD) [36]. The aim of the present review is to provide a summary of the recent literature exploring the relationship between quercetin and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…It also inhibits lipid peroxidation and platelet aggregation, and it stimulates mitochondrial biogenesis [32]. Several studies have reported on the neuroprotective effects of quercetin, both in vitro and in vivo models of neurodegenerative disorders, such as cognitive impairment [33], ischemia, traumatic injury [34], Parkinson's disease (PD) [35], and Huntington's disease (HD) [36]. The aim of the present review is to provide a summary of the recent literature exploring the relationship between quercetin and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin also has a role in rotenone-induced neurotoxicity in PD. Moreover, quercetin treatment reverses impaired autophagic activity and results in the protection of the brain against oxidative stress [186]. Furthermore, quercetin reduces PKCε/p38MAPK mediated ROS production through the activation of the ERK1/2 pathway to protect neurons from oxidative stress [187] and it is indicated that GSK-β and p38 inhibition or PKC activation results in Nrf2 phosphorylation under quercetin treatment [188].…”
Section: Polyphenols Act As Neuroprotective Agent During Pkc and Automentioning
confidence: 99%
“…In turn, flavonoids can be sub-classified into flavonols, flavones, flavanols, flavanones, anthocyanidins, and isoflavonoids, according to the structure of the heterocycle C ring. Examples of compounds which are mostly investigated for their potential neuroprotective effects include quercetin, kaempferol and myricetin (flavonols) [ 50 , 51 , 52 , 53 , 54 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], scutellarin, baicalein, and apigenin (flavones) [ 50 , 55 , 56 , 61 , 87 , 88 , 89 , 90 ], catechins, epicatechin, and epigallocatechin gallate (EGCG, flavanols), as well as genistein (isoflavonoid), and silymarin (flavonolignan) [ 63 , 91 , 92 , 93 , 94 , 95 , 96 ]. The stilbene group is best exemplified by resveratrol, a well-known phenolic compound found in red wine, grape, and virgin olive oil, which has shown remarkable neuroprotective and anti-aging properties in a plethora of experimental models [ 50 , 58 , 59 , 65 , 69 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: An Overview Of Neuroprotective Phytochemical Classesmentioning
confidence: 99%